The Knowledge of Science Teacher About Laboratory Based on Accreditation Status of State High Schools in Banda Aceh - Eka Maulina; Abdul Hamid; A Halim (Universitas Syiah Kuala, 2019)
This study aims to determine the teacher's knowledge of the science laboratory based on the accreditation status of Banda Aceh Public High School. In this study, the method used is the survey method.In this study, the population used was the teacher of Banda Aceh Public High School consisting of 8 schools. As for the sample, there were 54 people Biology, Physics and Chemistry in Banda Aceh High School.The instruments used for data collection in this study were teacher response questionnaires. To analyze data, researchers used a percentage statistical test. Based on the results of data analysis that has been done, it is found that there are differences regarding teacher knowledge of the science laboratory based on school accreditation status.Where the teacher's knowledge of the laboratory based on the accreditation status of A Banda Aceh Public High School is better with a percentage of 89,50% compared to the teacher's knowledge of the laboratory based on the B accreditation status of the Banda Aceh State High School with a percentage of 78.50%.So that it can be said that the teacher's knowledge of the laboratory based on its accreditation status has good knowledge